(untitled) (Orinoquia, 2016)
In Colombia, the municipalities of Cumbal and Potosí Department of Nariño house small trout producers whose problems refers to minimal process associativity and lack of technical processes, no implementation of administrative, accounting, financial, tax, technology and marketing that negatively affect their organizational dynamics and competitiveness. The purpose of the study was to determine the perceptions and associative organizational readiness of small trout producers Cumbal and Potosí. The research is explanatory survey techniques were, workshop and focus group interviews. The main results show distrust in associativity false political promises, use of names for projects outside their reality; little commitment, no teamwork, think of particular interests, there is no vision or associative sense, miscommunication, minimal cooperation, in terms of partnership interest 90 percent are willing to partner to increase productivity, market quality product, and greater visibility in the sector. With regard to their organizational units grouped perceptions there are fish in small associations without corporate image, they are aware of the need to acquire a formal structure and legality of their business; no administrative processes such as planning, control, accounting and financial management, capital investment is minimal, no borrowing capacity. The main conclusions stand out that organizational perceptions derive from personal experience, unaware administrative, accounting, financial and marketing processes; little control of the production process for trout, little leadership, legally constituted fear, come trout farming as a source of income rather than as a business opportunity. Around associative predisposition, there is distrust, lack of commitment, poor communication, poor management technology there, see the need to associate and work together to be more productive and competitive in the local, regional and national fish sector.